Training methodology for youth judo athletes (ages 10–14) in line with modern international competition requirements - Kryvytskyi, Artur (Педагогічна Академія: наукові записки, 2025)
The relevance of the study is determined by the need to improve the training system of junior judo athletes under conditions of increasing competition at international tournaments and rising demands for athletesʼ physical, technical, and psychological readiness. The age period of 10–14 years is considered the most sensitive for the development of basic motor and technical-tactical skills; however, it is also characterized by a high risk of overloads and premature specialization, which requires a scientifically grounded training methodology. The purpose of the article is to develop and scientifically substantiate a comprehensive methodology for training junior judo athletes (aged 10–14) in accordance with modern international requirements. The research methodology is based on the analysis and synthesis of scientific and methodological sources, pedagogical observation of the training process, a comparative analysis of the experience of leading international judo schools, and pedagogical modeling to determine the optimal ratio of general and specialized training. The research results enabled the establishment that the effectiveness of the training process for judo athletes aged 10–14 is ensured by a comprehensive approach that combines various areas of preparation. A methodology is proposed that provides for an optimal ratio of general physical training (55–60%), specialized technical-tactical training (25–30%), and tactical work (10–15%). It is based on the dominance of the general physical block, which creates a solid foundation for further athletic progress and injury prevention. This approach includes the gradual complication of specialized and tactical tasks to form stable motor patterns and the ability to apply techniques in competitive conditions. A distinctive feature of the methodology is the integration of traditional pedagogical approaches with modern technologies for monitoring athletesʼ physical condition and providing psychological support, which aligns with the international experience of leading judo schools (Japan, France, Brazil, Germany). It was found that such a combination ensures the harmonious development of physical, technical, and psychological components of preparation, forming the basis for steady improvement in performance at subsequent stages of sports development. The conclusions confirm that the proposed methodology enhances the performance of young judo athletes, contributes to the prevention of overloads, strengthens psychological resilience, and ensures a smooth transition to subsequent stages of sports training in line with international requirements. Prospects for further research lie in improving the individualization of the training process, studying gender aspects of preparation, and analyzing the long-term results of implementing the methodology in the practice of sports schools.